Capparis trisonthiae (Capparaceae), a new species from Thailand - Srisanga P. (2014)
A new species of Capparaceae, Capparis trisonthiae Srisanga & Chayamarit, from Doi Phu Kha National Park, Nan Province, northern Thailand, is described and illustrated. It belongs to Capparis sect. Monostichocalyx Radlk. and resembles C. klossii Ridl., endemic to the Isthmus of Kra in southern Thailand, but can be distinguished by several characters of the leaves and flowers.